Trypanosoma cruzi and Its soluble antigens induce NET release by stimulating toll-like receptors - Sousa-Rocha, Daniel [UNESP]; Thomaz-Tobias, Mariana [UNESP]; Diniz, Larissa Figueiredo Alves [UNESP]; Souza, Priscila Silva Sampaio [UNESP]; Pinge-Filho, Phileno; Toledo, Karina Alves [UNESP] (Public Library Science, 2015)
Neutrophils release fibrous traps of DNA, histones, and granule proteins known as neutrophil extracellular traps (NETs), which contribute to microbicidal killing and have been implicated in autoimmunity. The role of NET formation in the host response to nonbacterial pathogens is not well-understood. In this study, we investigated the release of NETs by human neutrophils upon their interaction with Trypanosoma cruzi (Y strain) parasites. Our results showed that human neutrophils stimulated by T. cruzi generate NETs composed of DNA, histones, and elastase. The release occurred in a dose-, time-, and reactive oxygen species-dependent manner to decrease trypomastigote and increase amastigote numbers of the parasites without affecting their viability. NET release was decreased upon blocking with antibodies against Toll-like receptors 2 and 4. In addition, living parasites were not mandatory in the release of NETs induced by T. cruzi, as the same results were obtained when molecules from its soluble extract were tested. Our results increase the understanding of the stimulation of NETs by parasites, particularly T. cruzi. We suggest that contact of T. cruzi with NETs during Chagas's disease can limit infection by affecting the infectivity/pathogenicity of the parasite.